Lentiviral vector common integration sites in preclinical models and a clinical trial reflect a benign integration bias and not oncogenic selection - Biffi, Alessandra; Bartholomä, Cynthia C.; Cesana, Daniela; Cartier, Natalie; Aubourg, Patrik; Ranzani, Marco; Cesani, Martina; Benedicenti, Fabrizio; Plati, Tiziana; Rubagotti, Enrico; Merella, Stefania; Capotondo, Alessia; et al. (Blood, 2011)
A recent clinical trial for adrenoleukodystrophy (ALD) showed the efficacy and safety of lentiviral vector (LV) gene transfer in hematopoietic stem progenitor cells. However, several common insertion sites (CIS) were found in patients' cells, suggesting that LV integrations conferred a selective advantage. We performed high-throughput LV integration site analysis on human hematopoietic stem progenitor cells engrafted in immunodeficient mice and found the same CISs reported in patients with ALD. Strikingly, most CISs in our experimental model and in patients with ALD cluster in megabase-wide chromosomal regions of high LV integration density. Conversely, cancer-triggering integrations at CISs found in tumor cells from γretroviral vector-based clinical trials and oncogene-tagging screenings in mice always target a single gene and are contained in narrow genomic intervals. These findings imply that LV CISs are produced by an integration bias toward specific genomic regions rather than by oncogenic selection.
Gesehen am 23.03.2022